ANALISIS KUALITAS DAN KUANTITAS KERJA KARYAWAN RECEPTIONIST DI ROCKY HOTEL PADANG - Selly Selfianita; Ira Meirina Choir (Jurnal Pariwisata Bunda, 2021)
This research was motivated by the presence of guest complaints about the quality and quantity of receptionist employees at Rocky Hotel Padang. The problem that appears is that the receptionist only gives keys to guests and does not explain the facilities at the hotel. There are still guest complaints about the employee's unfriendly attitude when serving guests checking in and checking out. The receptionist is not nimble when handling guests, so many guests queue  when checking in, lack of cooperation and communication between employees and receptionists. This study aims to describe: the quality of work and the  quantity of work. The type of this research was descriptive qualitative survey method and using purposive sampling. The sources of this research consist of 1 Spv receptionist at Rocky Hotel Padang, 1 Receptionist Manager for Rocky Hotel Padang, 3 employees for a receptionist at Rocky Hotel Padang. Based on the research results, some of the questions related to the quality and quantity of receptionist employees' work were found: 1) the quality of work of receptionist employees still lacks in completing work in accordance with the SOP. 2) The quantity of work of the receptionist employees is in accordance with the aspects of suitability, neatness, completeness. The results of the study suggest that the performance of receptionist employees still has aspects that have not followed the procedure for planning to improve performance at Rocky Hotel Padang. There are also plans to create an organization according to their respective work fields, both monitoring the performance of employees and superiors that will be made by Rocky Hotel Padang front office department.